Explicitness in science discourse: a Gricean account of income-related differences. (2nd January 2016) - Avenia-Tapper, Brianna; Isacoff, Nora M.
Abstract : Highly explicit language use is prized in scientific discourse, and greater explicitness is hypothesized to facilitate academic achievement. Studies in the mid-twentieth century reported controversial findings that the explicitness of text differs by the income and education levels of authors' families. If income-related differences in explicitness persist today, this may be one of the mechanisms by which parent income currently affects academic achievement. Therefore, this study reexamines the relationship between parent income and reliance on deictic terms, one proxy for explicitness, in the science writing of 100 5th grade students. Findings suggest that income-related differences in reliance on deictic terms persist in the twenty-first century, that students from low-income families are more 'novle' or assume a relatively less knowledgeable reader than students from higher income families, and that this novility is inversely related to science achievement. Implications for instruction are discussed.